Comparative assessment of antibacterial effect of two types of laser and their effect on morphology and mineral content of dentin - Soha Adel Abdou; Haythem S Moharrum; Elsayed Abdallah Eltayeb (Journal of the Arab Society for Medical Research)
Background/aim Scientists have proven that the main cause of endodontic diseases and failures is the existence of micro-organisms in the root canals and inside the dentinal tubules. So the aim of the study was to compare the antibacterial effect of Erbium, chromium-doped yttrium, scandium, gallium, and garnet (Er,Cr:YSGG) laser and diode laser 980 nm alone and in combination with 5.25% sodium hypochlorite (NaOCl) irrigant against Enterococcus faecalis biofilm and also compare their effect on the morphology and mineral content of root canal dentin by scanning electron microscope (SEM) and energy-dispersive X-ray spectroscopy (EDX) analysis. Materials and methods The specimens used in our study were fifty four extracted human single-rooted teeth. They were collected from the Dental Department of the Research Institute of Ophthalmology, Egypt. Mechanical preparation was done to all teeth after their crowns were removed. They were autoclaved, and after that, they were inoculated with Enterococcus faecalis for 30 days. Roots were divided into six groups (each=9) according to type of treatment. Group A: 5.25% NaOCl, group B: Er,Cr:YSGG laser, group C: 5.25% NaOCl and Er,Cr:YSGG laser, group D: diode laser 980 nm, group E: 5.25% NaOCl and diode laser 980 nm, in addition to control group: saline. Their antibacterial effect was assessed before and after treatment. Changes in the morphology and mineral content of root canal dentin were assessed by SEM and EDX. Statistical analysis was done. Results Group C had significantly the highest percentage of Enterococcus faecalis reduction (98.95%), followed by group E (98.04%), then group D (95.27%), then group A (94.65%), then group B (92.99%), while the control group had significantly the lowest percentage of Enterococcus faecalis reduction (0.22%). Regarding SEM results, group B and group D exhibited score 1 (88.9%), control group and group C score 3 (77.8%), group A score 4 (88.9%), and group E score 5 (88.9%). Regarding EDX results, group B was significantly the lowest in Ca/P ratio, while there was an insignificant difference between other groups. Conclusions Er,Cr:YSGG laser, and diode laser, when used without 5.25% NaOCl irrigant, produced less morphological changes to dentinal tubules, but when combined with 52.5% NaOCl irrigant, produced more antibacterial effect against Enterococcus faecalis. Lasers alone or combined with 5.25% NaOCl irrigant produced changes in the mineral content of root canal dentin.